Early infarct growth predicts long-term clinical outcome after thrombolysis - Cho, Kyung-Hee; Kwon, Sun U.; Lee, Deok Hee; Shim, WooHyun; Choi, ChoongGon; Kim, Sang Joon; Suh, Dae-Chul; Kim, Jong S.; Kang, Dong-Wha (Journal of the neurological sciences, 2012)
Ischemic lesion growth may be a surrogate marker of clinical outcome, but no such interrelationship after thrombolysis has yet been determined. We evaluated the association between early infarct growth on diffusion-weighted imaging (DWI) and long-term clinical outcome after thrombolysis. We retrospectively reviewed outcomes in patients with acute middle cerebral artery territory stroke who had been treated with intravenous tissue plasminogen activator or intra-arterial urokinase. DWI lesion volumes were measured at baseline and within 7days, and the difference was calculated. Clinical outcome was evaluated using the modified Rankin Scale (mRS) at 3months. Good and poor clinical outcomes were defined as: a) mRS 0–1 vs. mRS 2–6, b) mRS 0–2 vs. mRS 3–6, and c) responder analysis which was influenced by the baseline National Institutes of Health Stroke Scale (NIHSS) scores: good and poor outcomes were defined as mRS 0 vs. mRS 1–6 if the baseline NIHSS score was <8, mRS 0–1 vs. mRS 2–6 if the NIHSS score was 8–14, and mRS 0–2 vs. mRS 3–6 if the NIHSS score was >14. The relationship between the ischemic lesion volume change and clinical outcome was explored. The cut-off value of infarct growth predicting long-term outcome was estimated using receiver operating characteristic analysis. Of the 81 patients included, 67 (82.7%) showed lesion growth, and absolute growth was significantly related to poor outcomes (P<0.001 all for mRS 2–6, mRS 3–6, and responder analysis). Multivariate analysis showed that absolute lesion growth was an independent predictor of poor outcome, defined as mRS 2–6 (P=0.002; odds ratio [OR], 1.06; 95% confidence interval [CI], 1.02–1.10), mRS 3–6 (P=0.001; OR, 1.06; 95% CI, 1.02–1.10), and poor outcome by responder analysis (P=0.001; OR, 1.06; 95% CI, 1.03–1.10). The cut-off values of lesion growth that discriminated between good and poor outcomes were 14.11cm3 for mRS 2–6; 15.87cm3 for mRS 3–6; and 14.11cm3 in responder analysis. Early DWI lesion growth is an independent predictor of poor outcome after thrombolysis and may serve a potential surrogate marker of clinical outcome in acute stroke trials.